Analisis Pemerolehan bahasa ibu pada anak usia dini di Gampong Maunasah Papeun Aceh Besar - Siti Naila Fauzia; Syinta Herliyana; Fakhriah Fakhriah (Program Studi Bimbingan dan Konseling, FKIP, Universitas Syiah Kuala, 2020)
The acquisition of the mother tongue in this study is the use of regional languages which are used as a means of communication in the family. Early childhood is the initial age for forming habits in children, including in acquiring regional languages as the mother tongue which is commonly used in children's daily lives. In acquiring the mother tongue in children, it is necessary to know the suitability of language studies in the acquisition of the mother tongue, consisting of phonology, syntax, and semantics. The study aims to analyze the acquisition of mother tongue in early age children living in Gampong Meunasah Papeun, Aceh Besar District. The research was conducted using qualitative methods with data collection techniques, in the form of interviews with the parents and neighbors of the children concerned, as well as observations on 2 children aged 5-6 years who use the Acehnese language in their daily life. The results of the study show that the Acehnese language as the mother's language for children has been used in the family for a long time. Parents and the playing environments are examples and support for children. From the phonological side, it can be seen that the articulation of language in children is sometimes still not in accordance with the actual sound of the word. In the syntactic study, the child seems to have spoken in complete sentences in the Acehnese language but sometimes suffers from distortion. In the semantic study, children know the meaning of vocabulary and sentences in the Acehnese language, except for the Acehnese language which is rarely heard by children.Keywords: Mother Language Acquisition, Regional Language, Early Childhood ABSTRAKPemerolehan bahasa ibu pada penelitian ini adalah penggunaan bahasa daerah yang digunakan sebagai alat komunikasi dalam keluarga. Anak usia dini merupakan usia awal pembentukan kebiasaan pada anak, termasuk dalam pemerolehan bahasa daerah sebagai bahasa ibu yang biasa digunakan dalam keseharian anak. Pemerolehan bahasa ibu pada anak, perlu diketahui kesesuaian kajian bahasa dalam pemerolehan bahasa ibu tersebut, terdiri dari fonologi, sintaksis dan semantik. Penelitian ini bertujuan untuk menganalisis pemerolehan bahasa ibu pada anak usia dini yang tinggal di Gampong Meunasah Papeun, Kabupaten Aceh Besar. Penelitian dilakukan menggunakan metode kualitatif dengan teknik pengumpulan data, berupa wawancara dengan orang tua dan tetangga anak yang bersangkutan, serta observasi pada 2 orang anak usia 5-6 tahun yang menggunakan bahasa Aceh dalam kesehariannya. Hasil penelitian menunjukkan bahwa bahasa Aceh sebagai bahasa ibu pada anak, telah dibiasakan sejak dulu dalam keluarga. Orang tua dan lingkungan bermain menjadi contoh dan dukungan kepada anak. Pemerolehan bahasa Aceh pada anak dalam kajian fonologi, terlihat artikulasi bahasa pada anak terkadang masih belum sesuai dengan bunyi kata sebenarnya. Pada kajian sintaksis, anak terlihat sudah berbicara dengan kalimat lengkap dalam bahasa Aceh, namun terkadang mengalami gangguan distorsion. Pada kajian semantik, anak mengetahui makna kosa kata dan kalimat dalam bahasa Aceh, kecuali bahasa Aceh yang jarang didengar anak.